(untitled) (Proceedings of the International Conference on Future of Education, 2024)
This research aims to develop 3D augmented reality mathematics learning media with ethnomathematical concepts to support the independent learning program. Mathematic SASAMBO media products that have been developed are then tested for the validity and practicality of the media. The ethnomathematical elements used in this study are traditional houses originating from 3 tribes in West Nusa Tenggara, includingBale Lumbung from the Sasak Tribe, Istana Dalam Loka from the Samawa Tribe, and Uma Lengge from the Mbojo Tribe. This research adopts Research and Development (R&D) refers to the 4-D development model. The 4-D development steps are definition (define) which contains problem analysis, task analysis, and concept analysis; The second stage is design (design) by designing augmented reality media using ethnomathematical concepts with the help of Blender software version 2. 93, Adobe Illustrator artwork 23.0, and Unity and Vuforia AR Extension for Unity; The third stage is the development (DEvelop) by conducting feasibility tests and media practicality. The research sample was 61 students taken with a simple random sampling technique. Based on the results of the study, the average validity score by three validators gave a score of 91.67%, which indicates that the MAMBO media developed is very valid. The results of the media practicality test showed that students gave a positive response to all components of the MAMBO media with an average practicality of 82%. Based on the data obtained, it can be concluded that the MAMBO media developed has been very valid and very practical to be used in learning activities.